A Comprehensive Review On: Polycystic Ovarian Disease and It’s Impact on Health Care of Female - Rit, Shayantika; Kumar, Praveen; Trehan, Spardha (Journal of Neonatal Surgery, 2025)
Poly cystic ovarian disease (PCOD) is a complex pathophysiology and common endocrine, metabolic disorder that affect the ovaries and can lead to physiological, irregular menstrual cycle also the main reason of infertility and also formation of cysts in the ovary. It’s also know as Polycystric ovarian syndrome. PCOS is a hormonal condition that results in larger ovaries with little cysts around the periphery.This hormonal disorder globally affect the more then 5 - 15% ladies at their puberty age leading to decreasing the level of Oestrogen and Progesterone. They also have increasing the level of Androgen. This ovulation process stimulated by bodily hormone. The clear root of PCOS it’s genetic alliance and hormonal disbalance with most usual manifestation , acne on face, hirsutism, insulin resistance, hair loss, obesity. The acumen regarding management of PCOD through healthy life style with physical activity like Yoga. PCOS is considered focus on implement or modification in way of living style to the community (education, stop smoking, rational diet , not consumption of alcohol and weight management) when necessary are of the importance and early obstruction to fend off future morbidities.